Digital Competence Is The Basis Of A Successful Teacher's Activity - Artikova Muhayyo Botiraliyevna (International Journal on Integrated Education, 2023)
The article is devoted to the description of digital competencies of teachers working in the field of modern education. The article presents a certain structure of digital competencies, their analysis and a set of basic competencies that help to carry out successful pedagogical activities.